Profil Kondisi Fisik Peserta Ekstrakurikuler Bola Voli SMP Negeri 15 Palu - Nurfataya Pando'o; Tri Murtono; Nyoman Sukrawan; Christian Kungku; Delvi Kristanti Liloi (Jurnal Porkes, 2026)
This study aimed to determine the physical condition profile of volleyball extracurricular participants at SMP Negeri 15 Palu. The research employed a quantitative approach with a descriptive research design. The population consisted of all active volleyball extracurricular participants at SMP Negeri 15 Palu, totaling 20 students, who were selected using a total sampling technique. Data were collected through a series of physical fitness tests, including a 30-meter sprint, 30-second push-up test, 30-second sit-up test, sit and reach test, vertical jump test, 4 × 10-meter shuttle run, and 1000-meter run. The data were analyzed using descriptive statistics and converted into T-scores before being classified into predetermined categories. The results showed that the overall physical condition of the volleyball extracurricular participants was in the moderate category. The distribution of participants based on physical condition categories revealed that 1 participant (5%) was classified as very good, 4 participants (20%) as good, 8 participants (40%) as moderate, 6 participants (30%) as poor, and 1 participant (5%) as very poor. It can be concluded that the physical condition of volleyball extracurricular participants at SMP Negeri 15 Palu requires further improvement through well-planned, systematic, and continuous training programs to enhance performance and sports achievement.